Edukasi Bahaya Link Phishing Untuk Meningkatkan Kesadaran Keamanan Digital Pada Ibu-Ibu PKK - Rosmalia Anggraeni; Sandikha Bayu Pratama; Diva Nurhafizha Uswendi; Hifni Wafi Abiyya Achmad; Debi Sela; Latifah; Niko Ikmal Wirawan; Fitri Aulia Insani; Avila Marsa Salsabila; Mufida Salsabila; Alan Dharmawan; Shafa Ainun Nabila; Figih Roni Mahendra; Muhammad Kamal Burhanudin; Anaf Rafitno; Hidayatus Sibyan (CV. Multi Kreasi Media, 2026)
The rapid development of digital technology provides convenience in daily life but also increases the risk of digital crimes, one of which is phishing. Phishing is a fraudulent attempt that exploits fake links or messages to steal users’ personal information. Adults and the elderly, including PKK women, are considered vulnerable groups due to their high use of instant messaging applications without sufficient digital security awareness. This community service activity aims to enhance awareness and understanding of the dangers of phishing links among PKK women in Salam Village, particularly those spread through WhatsApp. A qualitative descriptive approach was employed through socialization activities and interactive discussions. Data were collected through observation, question-and-answer sessions, and documentation. The results indicate positive responses and improved participants’ understanding of phishing characteristics and preventive measures. Therefore, this digital security socialization activity is considered effective as a preventive effort to improve digital security literacy in rural communities.